NSQIP® Indexed Complications Following Transurethral Bladder Tumor Resection and Contemporary Financial Implications. Issue 5 (September 2018) - Caveney, Maxx K.; Brooks, David C.; Haddad, Devin A.; Kovell, Robert C.; Terlecki, Ryan P.
Abstract : Introduction: : We determined the incidence of NSQIP (National Surgical Quality Improvement Project) indexed complications by tumor size and investigated the related financial implications based on contemporary reimbursement schedules. Methods: : Transurethral bladder tumor resection procedures performed from 2010 to 2012 were identified and stratified by size specific CPT coding. Preoperative characteristics, surgical parameters and 30‐day perioperative outcomes were compared using chi‐square analysis and Student's t‐test. Financial data for all inpatient transurethral bladder tumor resections performed during the most recent fiscal year at our institution were collected and analyzed, and a comparison was made using up‐to‐date Medicare reimbursement schedules. Results: : We identified 8, 116 cases, including 3, 533 coded as small (43.3%), 2, 734 medium (33.5%) and 1, 849 large (22.6%). Large resections required longer operative time (small—25.8 minutes, medium—33.0 minutes, large—49.0 minutes, p <0.01) and length of stay (small—0.67 days, medium—1.1 days, large—1.9 days, p <0.006), and had higher rates of transfusion (small—0.74%, medium—1.5%, large—3.7%, p <0.001), sepsis (small—0.23%, medium—0.44%, large—0.92%, p <0.05), renal insufficiency (small—0.17%, medium—0.15%, large—0.60%, p <0.01) and 30‐day mortality (small—0.2%, medium—1%, large—1.8%, p <0.05) independent of preoperative parameters. Large resections were also associated with higher rates of 30‐day readmission (small—4.3%, medium—6.3%, large—9.4%, p <0.001) and reoperation (small—2.1%, medium—2.7%, large—4.5%, p <0.001). Institutional data demonstrate that the most common Diagnosis Related Group classification results in an operating loss when treating Medicare beneficiaries. Conclusions: : Urologist selected coding directly correlates with NSQIP indexed postoperative complications. Many cases of transurethral bladder tumor resection with associated complications may result in financial loss for the performing institutions. Efforts to improve quality of care and reimbursement seem warranted.